Analysis on air and ground surface temperatures in an active rock glacier area (Col d'Olen, Italy) - COLOMBO, NICOLA; FRATIANNI, SIMONA; GUENZI, DIEGO; ACQUAOTTA, FIORELLA; GIARDINO, Marco; PEROTTI, Luigi; FREPPAZ, Michele; GODONE, DANILO FRANCESCO; SAID PULLICINO, DANIEL; MARTIN, Maria; ISAIA, MARCO; E. Giaccone; et al. (Gaber Begeš, Jovan Bojkovski, Janko Drnovšek, Gregor Geršak, Drago Groselj, Domen Hudoklin, Andrea Merlone, Chiara Musacchio, Igor Pušnik, Francesca Sanna, 2014)
Rock glaciers are the most prominent geomorphic features of alpine permafrost, resulting from creeping accumulations of debris saturated by ice (Barsch, 1996; Schoeneich et al., 2011). In this work the active Col d’Olen rock glacier, located in Aosta Valley Region on the boundary line with Piemonte Region (NW Italian Alps), has been analysed. The rock glacier typology is talus-tongue shaped and the elevation of the front is ca. 2710 m asl, covering a total area of ca. 42,000 m2. Climatic data from automatic weather station located in the rock glacier area (Col d’Olen station, 2900 m asl) have been used to analyse the main characteristics of the local climate on hourly, daily, monthly, seasonal and annual basis. Climatic trends and indexes have been also calculated. Particular attention has been paid to mean annual air temperature (MAAT), summer air temperature, winter air temperature, frost days, ice days, freeze-thaw days and winter/spring snow precipitations (fresh snow and snow depth). Moreover, meteorological data have been collected by installing portable instruments on the rock glacier’s body, integrated in a Mini Automatic Weather Station. The ground temperature monitoring has been conducted using dataloggers installed at 5/10 cm of depth, to measure the ground surface temperature (GST). The main parameters analysed are: mean annual ground surface temperature (MAGST), variability of MAGST on rock glacier’s surface, WeqT, shallow temperature of ground in summertime (STG), snow onset day, snow melt-out date, basal-ripening day and ground freezing index (FrezInd). These analysis has been conducted by installing Maxim iButton® DS1922L mini-thermocrons and Hobo TidbiTv2 temperature loggers regularly distributed on the rock glacier’s surface and in a few selected surrounding sites. The overall objective of the present research is to provide a complete view of the interconnections among climate and permafrost in the context of an alpine permafrost area characterised by the presence of an active rock glacier, ...